Jelajah Sultra: Inovation Of UI/UX Design for Smart Tourism App with AI-Based Travel Assistant to Support SDG 8 - Rahmat Saputra, La Ode Alvin; Saputra, Rizal Adi; Ramadhan, Muh. Akbar Perdana (IC-ITECHS, 2024)
The Jelajah Sultra application is a conceptual digital innovation designed to promote sustainable tourism in Southeast Sulawesi by incorporating an AI-powered smart travel assistant and optimal UI/UX design principles. This initiative addresses the growing demand for user-friendly and efficient digital platforms in the tourism sector, particularly in response to increasing tourist numbers in Indonesia. The primary aim of this study is to develop a UI/UX design concept for a tourism application that supports sustainable tourism practices, enhances local economic growth, and empowers communities by improving market accessibility. Utilizing the Design Thinking method, this research involves the stages of empathizing, defining user needs, ideating, prototyping, and testing to create a user-centric design for Jelajah Sultra. The design incorporates features such as AI-powered chatbot assistance, interactive maps, and streamlined navigation to ensure a superior user experience. The usability testing resulted in a high usability score of 94.0, indicating the potential of Jelajah Sultra to facilitate seamless information delivery and effective interaction for users. This research contributes to SDG 8 by fostering local economic growth and supporting responsible tourism practices.